Comparison of the effect of chronic treatment of mitragynine and morphine on antinociceptive behaviour and cAMP-PKA RIIβ genes expression in mice - Akhir, Sakinah Mohd (2018)
Title: Comparison of the Effect of Chronic Treatment of Mitragynine and Morphine on Antinociceptive Behaviour and cAMP-PKA RIIβ Genes Expression in Mice Background: Mitragynine is an opioid agonist similar to morphine. Chronic administration of morphine is shown to increase the expression of cAMP-PKA RIIβ responsible for the development of tolerance. There were no previous studies done on the effect of chronic mitragynine administration on cAMP-PKA RIIβ gene expression. Therefore, this study aims to evaluate the development of tolerance in mice chronically treated with morphine and mitragynine, assessed by 1) antinociceptive behavior and 2) cAMP-PKA RIIβ gene expression. Methods: A total of 39 Swiss albino mice were randomized into 3 groups, each of which received daily subcutaneous injection of either mitragynine, morphine or placebo, in escalating dose for 9 days. The development of tolerance was assessed by 1) Antinociceptive behaviour study: Antinociceptive response to thermal noxious stimuli was evaluated daily using hot plate test at 52⁰C (52±2⁰C), 30 minutes after drug administration, until the signs of pain (hind-paw licking, jumping) exhibited. The antinociceptive response was quantified as a percentage of maximal possible effect (%MPE) and reduction in mean %MPE more than 50% was used for assessment of antinociceptive tolerance. 2) Molecular study: The cerebral tissues (thalamus, medulla, PAG) were dissected for sampling in order to determine cAMP-PKA RIIβ gene expression using semiquantitative PCR method. Results: Mitragynine-treated mice did not show tolerance by day 9 when compared to placebo (p<0.01), similar to morphine. However, at molecular level, the cAMP-PKA RIIβ gene expression for morphine was enhanced compared to mitragynine and placebo. Conclusion: Chronic treatment with mitragynine did not show development of tolerance on antinociceptive behavior and cAMP-PKA RIIβ gene expression, same as placebo, whereas morphine showed an increased in expression of cAMP-PKA RIIβ gene despite no behavioural antinociceptive tolerance.